Otogenic Meningitis or Meningoencephalitis in 30 Dogs: Association Between Neurological Signs, Magnetic Resonance Imaging Findings, and Outcome - Meritxell Moral; Carlos Blanco; Valentina Lorenzo (Veterinary Sciences)
This retrospective study aimed to assess the accuracy of neurological examination in identifying intracranial extension of ear infection in dogs and to investigate the clinical data that may potentially aid in its diagnosis and prognosis. Dogs diagnosed with meningitis or meningoencephalitis due to an intracranial extension of otitis media-interna were included, and the relationship of MRI findings with neurological examination, clinical data, and outcome was studied. Thirty dogs were included, with 96% corresponding to brachycephalic breeds and a mean age of 7.5 years. The neurological examination was accurate in localizing the lesion in the central nervous system in 33% of dogs. Dogs with brainstem parenchymal involvement in magnetic resonance imaging (MRI) had a longer recovery (21 days). Recovery was complete in 28% of cases, with dogs more likely to have persistent neurological deficits when parenchymal and/or meningeal involvement was observed on imaging. MRI did not show intracranial extension in 20% of cases despite inflammatory cerebrospinal fluid (CSF). This study supports the conclusion that intracranial extension of otogenic infection is possible in dogs without central nervous system signs. When otitis media-interna is diagnosed, MRI and CSF studies should be recommended, especially for chronic or recurrent cases and in brachycephalic breeds.